How useful is the concept of transit migration in an intra-Schengen mobility context? Diving into the migrant smuggling and human trafficking nexus in search for answers - Massol de Rebetz, Roxane de (European journal on criminal policy and research, 2021)
When using the concept of transit migration, contemporary scholarly literature and policy documents typically refer to situations located outside or at the outskirts of the European Union. By analyzing the critical and empirical scholarship which uncovers the so-called gray area where it becomes hard to make clear distinctions that can be found at the nexus between migrant smuggling and human trafficking, the article aims to shed new light on the real-life vulnerabilities and dynamics that do not fit prototypical legal categories of either human trafficking or migrant smuggling. In so doing, the article discusses and analyzes legal and empirical scholarship that uncovers these vulnerabilities. The vulnerabilities observed are likely to be further enhanced in transit zones where stranded individuals within the EU aim to continue their (increasingly) fragmented/non-linear migration journeys. Therefore, the article proposes to consider the usefulness and the usage of the notion of “transit migration” in the context of Intra-Schengen border mobility and not just when discussing external border mobility. The article argues that the concept of transit migration, if carefully defined, and if particular vulnerabilities found in transit space are recognized, can serve as a helpful lens that can prevent falling into the trap of conceiving migrant smuggling and human trafficking as strictly separate phenomena.